3 - The Turbulent 2010s: A Historical Draft - Zeleza, Paul Tiyambe (Africa Development, 2020)
The 2010s was an exceptionally turbulent decade characterised by complex and contradictory changes at local, regional and global levels. The changes encompassed all spheres from the political to the economic, as well as the social, cultural, and environmental dimensions of global society. This article identifies and analyses six key trends in the historical trajectory of the period. First, the decade was marked by intense political polarization in many countries; second, was the democratic recessions and resistance in some climes; third, was the rising economic inequalities and disequilibrium; fourth was the shift in global hierarchies and hegemonies; fifth, was the emergence of surveillance capitalism; and the final one was the rebellion of nature as evident in extreme weather conditions and global struggles over climate change. In analysing these key trends the article seeks to make sense of the messy complexities, mind boggling contradictions and massive changes of the various historical conjunctures of modernity.